FENOMENA DISFUNGSIONAL AUDIT - Emma Saur Nauli Sipayung; Dhea Erka Zahara; Ice Nasyrah Noor (Media Riset Akuntansi, Auditing & Informasi, 2021)
This study aims to examine the determinant factors of dysfunctional audit behaviour. This analysis used job stress and technical competence of auditors as an independent variable, dysfunctional audit behavior as dependent variable, and personality traits from The Big Five Personality theory and locus of control as moderating variables. The samples used in this study were auditors who work in public accounting firm in the region of DKI Jakarta. The results show that job stress has a positive effect on dysfunctional audit behaviour, the technical competence of the auditor has a negative effect on dysfunctional audit behaviour. In addition, personality traits of neuroticism and external locus of control reinforce positive effects of job stress on dysfunctional audit behaviour. Meanwhile personality traits openness to experience and internal locus of control were able to weaken the relation of job stress to dysfunctional audit behaviour. Then, other personality traits such conscientiousness, extraversion, and agreeableness do not weaken the positive effect of job stress with dysfunctional audit behavior. This indicates that the auditor's technical competence, personality traits and locus of control are important to reduce the likelihood of dysfunctional audit behavior.Penelitian ini bertujuan untuk menguji faktor-faktor determinan yang mempengaruhi perilaku disfungsional audit. Penelitian ini menggunakan stres kerja dan kompetensi teknis auditor sebagai variabel independen, perilaku disfungsional audit sebagai variabel dependen serta sifat kepribadian dari The Big Five Personality dan Locus of Control sebagai variabel moderasi. Sampel yang digunakan adalah auditor yang bekerja di Kantor Akuntan Publik wilayah DKI Jakarta. Sampel penelitian ini berjumlah 130 responden. Hasil penelitian menunjukkan bahwa stres kerja berpengaruh positif terhadap perilaku disfungsional audit, kompetensi teknis auditor berpengaruh negatif terhadap perilaku disfungsional audit. Selain itu, sifat kepribadian neuroticism dan locus of control eksternal yang memperkuat pengaruh positif stres kerja dengan perilaku disfungsional audit. Sedangkan sifat kepribadian openness to experience dan Locus of control internal memperlemah hubungan positif stres kerja terhadap perilaku disfungsional audit. Kemudian, Sifat kepribadian lainnya seperti conscientiousness, extraversion, dan agreeablesness tidak memperlemah pengaruh positif stres kerja dengan perilaku disfungsional audit. Penelitian ini menunjukkan bahwa kompetensi teknis auditor, sifat kepribadian dan locus of control berperan penting untuk mengurangi kesempatan melakukan perilaku disfungsional audit.